Combined astigmatic keratotomy and conductive keratoplasty to correct high corneal astigmatism. Issue 5 (May 2015) - Sy, Mary Ellen; Kovoor, Timmy A.; Tannan, Anjali; Choi, Daniel; Deng, Sophie X.; Danesh, Jennifer; Hamilton, Rex D.
Abstract : Purpose : To determine the safety, efficacy, and predictability of combined astigmatic keratotomy (AK) and conductive keratoplasty (CK) for treating high corneal astigmatism. Setting : University of California–Los Angeles, Los Angeles, California, USA. Design : Retrospective case series. Methods : From January 1, 2004, to December 31, 2009, AK and CK were performed in eyes with corneal astigmatism of 5.0 diopters (D) or more after keratoplasty or trauma. The uncorrected (UDVA) and corrected (CDVA) distance visual acuities, spherical equivalent (SE), defocus equivalent, mean astigmatism, efficacy index, and complications were evaluated. Results : In 11 eyes of 11 patients, the mean UDVA improved from 1.54 logMAR ± 0.50 (SD) preoperatively to 0.69 ± 0.62 logMAR 3 months postoperatively ( P < .001) and the mean CDVA from 0.55 ± 0.62 logMAR to 0.12 ± 0.11 logMAR ( P = .028). The mean SE and mean defocus equivalent decreased from −1.25 ± 5.06 D to 3.13 ± 3.06 D ( P = .15) and from 7.98 ± 4.41 D to 6.97 ± 3.73 D ( P = .45), respectively; these changes were not statistically significant. The mean absolute astigmatism decreased from 10.25 ± 4.71 D to 4.31 ± 2.34 D ( P < .001). The mean absolute orthogonal and mean oblique astigmatism showed a statistically significant decrease. The efficacy index was 0.82. One case of wound gape after AK required suturing. No infectious keratitis, corneal perforation, or graft rejection occurred. Conclusions : Results indicate that combined AK and CK is safe and effective for correcting high corneal astigmatism after surgery or trauma. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.